2023
DOI: 10.1007/s00380-023-02296-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of serum NT-proBNP (fragments 1-76aa and 13-71aa) and galectin-3 in predicting death and re-hospitalisation due to cardiovascular events in patients with heart failure

Abstract: Patients with heart failure (HF) are at a higher risk of rehospitalisation. In this study, we investigated the prognostic utility of galectin-3 (Gal-3) and NT-proBNP fragments (1-76aa and 13-71aa) as biomarkers to predict outcomes for patients with HF. We collected blood samples from patients with HF (n = 101). Gal-3 and NT-proBNP fragments (1–76aa and 13–71aa) concentrations were measured by immunoassay. Survival analysis and Cox proportional regression models were used to determine the prognostic utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, a more recent cohort study indicated that in HF patients or those at the risk of HF, before first hospitalization, GDF-15 grants specific information and is highly predictive of hospitalization for HF or all-cause death rate, contributing to more precise risk assessment that can better guide clinical decision making [80]. In addition to NPs, galectin-3 has been suggested as an important biomarker to stratify HF patients [82].…”
Section: Neurohormonal Biomarkersmentioning
confidence: 99%
“…Interestingly, a more recent cohort study indicated that in HF patients or those at the risk of HF, before first hospitalization, GDF-15 grants specific information and is highly predictive of hospitalization for HF or all-cause death rate, contributing to more precise risk assessment that can better guide clinical decision making [80]. In addition to NPs, galectin-3 has been suggested as an important biomarker to stratify HF patients [82].…”
Section: Neurohormonal Biomarkersmentioning
confidence: 99%